Leadership and its Contribution to Achieving Organizational Loyalty An Applied Study on Employees of the Saudi Electricity Company in the Jeddah Region (The International Journal for Scientific Research, 2024)
The study aims to provide a clear and comprehensive definition of the concept of entrepreneurship in the organizational context, identify the main characteristics that distinguish entrepreneurs in work environments, and measure the level of organizational commitment among employees of the Saudi Electricity Company in the Jeddah region. It also seeks to analyze the factors that affect the level of organizational commitment in the organization, diagnose the reality of entrepreneurship characteristics in it, and identify the foundations for enhancing organizational commitment. It also aims to analyze the impact of entrepreneurship characteristics on organizational commitment and diagnose the extent of differences in degrees of organizational commitment according to the entrepreneurial characteristics of decision makers. The study relied on the descriptive approach using a descriptive design and a questionnaire as the main tool for collecting data, as 120 questionnaires were distributed and 49 of them were retrieved. The study reached several results, including the Saudi Electricity Company in Jeddah's appreciation of innovations and suggestions submitted by employees, the need to improve employee motivation to present new ideas, provide a work environment that stimulates creative thinking, and organize training courses to develop innovation skills. The results also showed the impact of leadership on organizational loyalty, as most employees feel a sense of belonging and loyalty to the company, and there is satisfaction with the work environment and the appreciation they receive, with the need to improve some factors to enhance this feeling.
Keywords: Leadership; Organizational Loyalty; Employee Loyalty; Saudi Electricity Company